Effective Teaching Practices for Success During COVID 19 Pandemic: Towards Phygital Learning - Chaturvedi, Shakti; Purohit, Sonal; Verma, Meenakshi (Frontiers in Education, 2021)
Following the outbreak of COVID 19 in February 2020, Indian universities were shut down and used digital platforms to teach their students since then. Drawing from Kolb's Learning Theory, John Dewey's theory, Jack Mezirows transformative learning theory, and Jean Piaget's theory, the authors in this paper offer a viewpoint on some of the practical teaching practices which can be adapted in business schools in India to be successful in this emerging blended or phygital environment. Using a Community of Inquiry (CoI) framework, the authors reflect on the effective teaching practices based on his own experience, theoretical knowledge gained from an exhaustive web search of various databases of the period, particularly from February to August 2020. They concluded seven principal teaching methods to create an effective blended environment for students and faculties in Indian business schools: a) reframing virtual spaces in India through online knowledge repository and virtual labs b) using reflective thinking for andragogical and pedagogical Indian approach c) Indian teachers' readiness to offer various genres of courses on demand d) reinforcing resilience in Indian schools through meaningful participation and conflict resolution e) purposeful learning and inquiry-based learning for Indian students f) experiential learning through an inclusive online pivot in India g) useful apps are discussed to reach out to Indian parents community. These initiatives can influence academicians, educationists, podcasters, and the entire teacher fraternity to design an efficient and adequate teaching plan for the student community in India.